How regional climate and seed traits interact in shaping stress–tolerance of savanna seeds?. Issue 4 (2nd December 2021) - Ribeiro, Leandro C.; Barbosa, Eduardo R. M.; Borghetti, Fabian
Abstract: Functional traits related to regeneration responses to the environment are highly determinants of distribution patterns of plant communities. A large body of studies on seed traits suggests that regional climate may act as a strong filter of plant recruitment; however, few studies have evaluated the relative importance of seed traits and environmental filters for seed persistence at the population level. We tested the role of seed mass, water content and desiccation tolerance, as well as the germination time as proxies for seed tolerance to environmental filters (water deficit, heat shock and high temperatures) by comparing the response of tree species co-occurring in savannas located in different regions: Cerrado biome of Central Brazil and the Rio Branco savannas of northern Brazil. Seeds collected in savannas of Rio Branco showed a higher tolerance to environmental filters than those collected in savannas of the Cerrado. While the germination percentages largely varied in response to the treatments, the germination times were virtually unaffected by them, irrespective of seed origin, seed mass and water content. At the population level, the regional environment was a key determinant of seed tolerance to stress, irrespective of seed traits. Germination time was shown to represent a conservative seed trait and more linked to a species-specific germination strategy than to regional characteristics. Our results suggest that recruitment patterns of Cerrado savannas may be more impacted than Rio Branco savannas by the climate scenarios predicted for the future.